Pengelolaan Sampah Berbasis Masyarakat Melalui 3R Dalam Upaya Pengurangan Jumlah Timbulan Sampah - Paramita Dwi Sukmawati (LPPM STIKES Guna Bangsa Yogyakarta, 2021)
Waste management that is currently being carried out is still limited to collecting, transporting and disposing of waste without any efforts to reduce the amount of waste generated. The impact is that the amount of waste generation increases and only ends up in the final waste processing site (Landfill), thus affecting the health of the environment around the landfill site. For this reason, it is necessary to reduce the amount of waste generated, by means of community-based waste management through 3R (Reduse, Reuse and Recycle). The purpose of this activity is to disseminate information on how to manage community-based waste through 3R so that teachers, employees and students of SMK Negeri 6 Yogyakarta can play an active role in waste management. The method of implementing the activity uses the lecture and discussion method. The results of this activity are still short-term results, that is by looking at the enthusiasm of the participants during the question and answer time and discussion. Therefore the results of this activity still require follow-up activities that is mentoring activity waste management, so that SMK Negeri 6 Yogyakarta can implement community-based waste management through 3R.